I Am Non-Looking English Language Teacher: Reclaiming South Asian ELTs’ Identity in Japan - Regmi, Deepak (Journal of NELTA, 2025)
This qualitative study explores how South Asian English Language Teachers (ELTs) in Japan construct and negotiate professional legitimacy in the context of ongoing native speakerism, racialized assumptions, and shifting institutional practices. Drawing on semi-structured interviews with 22 South Asian ELTs working across diverse educational settings, the research employs a narrative inquiry and thematic analysis to explore how these educators construct and navigate their professional identities. The findings revealed that professional legitimacy is shaped not only by linguistic competency and teaching qualifications but also deeply influenced by perceptions of race, country of origin, and accent. While some teachers face ongoing challenges related to native-speakerism, institutional biases, and ambivalence regarding their status, some actively reclaimed their professional identities by embracing localized English varieties and positioning themselves as legitimate, culturally responsive educators. The policy shifts and institutional openness for diversity off er signs of hope, but the monolingual ideologies and native speaker hierarchies remain entrenched in Japan’s ELT landscape. The study concludes that professional identity formation for South Asian ELTs is a dynamic process of resistance, adaptation, and self-assertion, and underscores the need for systemic change to support genuine inclusion and professional recognition of diverse ELTs.